Lack of CYP3A4 protein induction despite mRNA induction in primary hepatocytes exposed to rifabutin as a possible explanation for its low interaction risk in vivo - Nilles, Julie; Theile, Dirk; Weiß, Johanna; Haefeli, Walter E.; Ruez, Stephanie (Archives of toxicology, 2024)
Rifampicin is a strong inducer of cytochrome P450 (CYP3A4) and P-glycoprotein (P-gp/ABCB1), leading to profound drug-drug interactions. In contrast, the chemically related rifabutin does not show such pronounced induction properties in vivo. The aim of our study was to conduct a comprehensive analysis of the different induction potentials of rifampicin and rifabutin in primary human hepatocytes and to analyze the mechanism of potential differences. Therefore, we evaluated CYP3A4/ABCB1 mRNA expression (polymerase chain reaction), CYP3A4/P-gp protein expression (immunoaffinity-liquid chromatography-mass spectrometry, IA-LC-MS/MS), CYP3A4 activity (testosterone hydroxylation), and considered intracellular drug uptake after treatment with increasing rifamycin concentrations (0.01-10 µM). Furthermore, rifamycin effects on the protein levels of CYP2C8, CYP2C9, and CYP2C19 were analyzed (IA-LC-MS/MS). Mechanistic analysis included the evaluation of possible suicide CYP3A4 inhibition (IC50 shift assay) and drug impact on translational efficiency (cell-free luminescence assays). Rifabutin accumulated 6- to 15-fold higher in hepatocytes than rifampicin, but induced CYP3A4 mRNA comparably to rifampicin (e. g. rifampicin 61-fold vs. rifabutin 44-fold, 72 h). While rifampicin for example enhanced protein (10 µM: 21-fold) and activity levels considerably (53-fold), rifabutin only slightly increased CYP3A4 protein expression (10 µM: 3.3-fold) or activity (11-fold) compared to rifampicin after 72 h. Both rifamycins similarly influenced expression of other eliminating proteins. A potential CYP3A4 suicide inhibition by a specific rifabutin metabolite or disruption of ribosome function were excluded experimentally. In conclusion, the lack of protein enhancement, could explain rifabutin's weaker induction-related drug-drug interaction risk in vivo.